Treasure Island!!! - Levine, Sara (Europa Editions, 2012)
"When a college graduate with a history of hapless jobs (ice cream scooper; gift wrapper; laziest ever part-time clerk at the Pet Library) reads Robert Louis Stevenson's novel Treasure Island, she is dumbstruck by the timid design of her life. ... Convinced that Stevenson's book is cosmically intended for her, she redesigns her life according to its core values: boldness, resolution, independence, and horn-blowing. Accompanied by her mother, her sister, and a hostile Amazon parrot that refuses to follow the script, our heroine embarks on a domestic adventure more frightening than anything she'd originally planned"--Book jacket flap.